Carbon dioxide adducts from DOPO‐grafted polyethylenimines as both blowing agents and flame retardants for polyurethanes. Issue 33 (8th April 2021) - Zeng, Jianming; Luo, Wenli; An, Jianing; Xie, Xingyi
Abstract: The high risk of flammability of polyurethane foams (PUFs) and the high global warming potentials of polyurethane (PU) blowing agents rank key problems to be solved in PUF industry. Herein, 9, 10‐dihydro‐9‐oxa‐10‐phosphenanthrene‐10‐oxide (DOPO)‐grafted polyethylenimines (PEIs) are synthesized via Atherton–Todd reaction, with grafting rate ranging from 13.3% to 28.3%. The grafted PEIs further react with CO2 to obtain corresponding CO2 adducts (DOPO‐PEI‐CO2 s). On the one hand, these CO2 adducts can disperse into PU foaming mixture to release CO2 as a climate‐friendly blowing agent. The resultant PUFs possess a density about 56 kg m −3 and a compressive strength over 200 kPa, suitable for some industrial applications. On the other hand, the DOPO grafting endows the PUFs with moderate flame retardancy, increasing the PUFs' limiting oxygen index value from 19.7 to 25 vol%, and decreasing the horizontal burning speed from about 360 mm min −1 down to 130 mm min −1 . This study for the first time provides a type of polyurethane (PU) raw material that can serve as both blowing agents and flame retardants. Abstract :